Reaction Mechanism and Properties of Cement-Based Materials (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
Cement is one of the most important building materials and is used to build various infrastructures due to its high strength, durability, and relatively low cost. The microstructure of cement-based materials comprises a cement paste system, stone, porosity, water content, and other components. Among the cement-based materials, the cement paste system, mainly the hydration product of clinker or a reaction precursor, is the most important. The microstructure of reaction products, pores, and the constituent phase and the hardening process of the cement paste system have a crucial influence on the mechanical and physical properties of the resulting materials. An in-depth understanding of the relationship between the microstructure and macroscopic properties of cement-based materials helps in the design of more efficient and stable cementitious materials for construction. Cement-based materials are multi-phase and multi-scale structures, and each component has a different degree of influence on the overall mechanical and physical properties. The Special Issue “Reaction Mechanism and Properties of Cement-Based Materials” includes the current research, application, and development of strengthening, toughening, and durability enhancement components of different scales of cement-based materials, reaction mechanisms, and properties of various cementitious materials, including Portland cement, aluminate cement, sulfate aluminum cement, ferroaluminate cement, and phosphate cement.